Struktur komunitas serangga herbivora dan parasitoid pada polong tanaman kacang-kacangan (Fabaceae) di Padang - Hasmiandy Hamid (Jurnal Entomologi Indonesia, 2012)
Abundance and diversity of herbivorous insects are not only determined by the trophic level above, but also can be affected by the trophic level below it. This research aims to study the community of herbivorous insects and parasitoids on pods of different types of legume crops in Padang. The method used in this study was a survey method. This method was done by collecting pods of legume plants in various habitats. Insects contained in pods were maintained until adulthood. Individual insects that did not emerge from the pods were removed by dissecting pods. This method was also used to estimate the number of seeds, good seeds were damaged or not damaged in each pod. The results of this study indicated that the composition of herbivorous insects on legumes, especially legume Crotalaria striata was dominated by Eucorynus crassicornis, while the parasitoid composition was dominated by Braconidae. E. crassicornis has a wider range of expansion compared to other herbivorous insects. The insects were found on three types of legum C. striata, Crotalaria sp., and Leucaena leucocephala, whereas other types of herbivores attack only two types of legumes. The highest percentage of damage was obtained in Crotalaria striata i.e 74.53%.